Relationships, unity and strength of Pak Nam Pho’s Taonang - Lertsawaengkit, Nawat; Rattanarungsikul, Phuvanart (Humanities, Arts and Social Sciences Studies, 2023)
This article was compiled to gather the basic knowledge and understanding of necessary information for designing creative works of visual arts from cultural studies related to the Chinese-Thai community in Pak Nam Pho district, Nakhon Sawan province, Thailand. Data were obtained from literature reviews together with field repositories by interviewing representatives of the successors in Chinese cultural activities. This article aims to research the process of recruiting, operating, and allocating positions for Pak Nam Pho’s Taonang, a traditional organizing committee, during the Chinese New Year festival by interviewing members of the Taonang and a representative from the Chinese Cultural Association of Pak Nam Pho, one of the biggest Chinese communities in Thailand. The Taonang consists of people of different ages, genders, and occupations who are approachable representatives of society and collaborate respectfully with other organizations. The recruitment and selection system of Pak Nam Pho’s Taonang committee does not limit the right of membership to only Chinese descendants or Chinese cultural successors, but rather, extends to Thai-Buddhists as well as other demographics in the Pak Nam Pho area. In short, each year, this system encourages diversity among Taonang members by shifting the processes of qualification away from racial requirements toward membership through spatial requirements, which has impacted how the Chao Pho-Chao Mae Pak Nam Pho Parade adjusts itself with every generation of Pak Nam Pho members. It is not surprising that the event tends to develop gradually year by year, however, these are still relatively minor details, allowing ancient traditions to remain at the core.